2,3-Dihydropyridin-4(1H)-ones and 3-Aminocyclohex-2-enones: Synthesis, Functionalization, and Applications to Alkaloid Synthesis - Seki, Hajime; Georg, Gunda I. (Synlett, 2014)
This account summarizes our recent investigations into the chemistry of 2,3-dihydropyridin-4(1H)-ones and 3-aminocyclohex-2-enones (enaminones). These enaminones are exceptionally versatile chemical scaffolds that serve as valuable intermediates in the synthesis of indolizidine and quinolizidine alkaloids and other bioactive compounds. Since we reported our first method for constructing enaminones in 2006, we have developed a number of additional approaches to the synthesis and derivatization of enaminones and we have explored their applications in natural product synthesis.1 Background2 Ynone Cyclization2.1 Initial Discovery2.2 Optimization of Reaction Conditions2.3 Scope and Limitations2.4 Mechanistic Studies2.4 Application to Quinolone Synthesis2.6 N-Butoxycarbonyl β-Lactam Approach2.7 Synthesis of 3,4-Dihydro-1,2-oxazepin-5(2H)-ones and Their Conversion into Enaminones3 Ketene Cyclization3.1 Chiral-Pool Approach3.2 Three-Component Synthesis4 C5 Functionalization4.1 Suzuki Coupling of Iodoenaminones4.2 Suzuki-Type Direct Cross-Coupling4.3 Suzuki-Type Direct Cross-Coupling with Arylboronic Acids4.4 Hiyama-Type Direct Cross-Coupling4.5 Direct Coupling with Aryl Iodides4.6 Alkenylation by the Fujiwara–Moritani Reaction4.7 Alkenylation of Uracils4.8 Aerobic Alkenylation and its Application to the Synthesis of 1,3,5-Trisubstituted Benzenes4.9 Lithium Perchlorate-Catalyzed Alkylation5 Applications to Total Synthesis5.1 Total Synthesis of (+)-Ipalbidine and (+)-Antofine5.2 Total Synthesis of (R)- and (S)-Boehmeriasin A5.3 Total Synthesis of Tylocrebrine and Related Phenanthropiperidines6 Summary and Outlook
Keywords: heterocycles; enaminones; alkaloids; natural product synthesis